Use of infrared thermography to evaluate the influence of the of Climatic Factors in the Reproduction and Lactation of Dairy Cattle - Chacur, Marcelo George Mungai; Bastos, Guilherme Pepino; Vivian, Dougles Sanches; da Silva, Leandro; Chiari, Luana Nayara de Freitas; Araujo, Juliana de Souza; Souza, Camila Dutra de; Filho, Luis Roberto Almeida Gabriel (Acta Scientiae Veterinariae, 2016)
Background: The digital infrared imaging thermography is a non-invasive imaging exam of easy performance accurately to measure temperatures of the areas of the animals body. The objective was to study the physiological variations of the surface temperature of the mammary gland, vulva, pelvis, thorax and abdomen with digital infrared imaging thermography in negative dairy cattle with California mastitis test (CMT) in different seasons, and the influence of climatic factors in these temperatures. Materials, Methods & Results: Eighteen Holstein cows, pregnant and non pregnant were used, negative for the California Mastitis Test, grazing on Urochloa decumbens pasture, receiving 2 kg of corn / animal / day, mineral mix and ad libitum water. Infrared thermography was performed every 30 days, for five months: January, February, March, April and May with thermographic camera (E40®, FLIR, Sweden) in the areas of the body: vulva, mammary gland, pelvis, abdomen and thorax. The thermal images (thermograms) were processed using the Flir Tools 2.1® program. The climatic factors: room temperature and relative humidity were monitored with globe thermometer (ITitwtg 2000®, Instrutemp, Brazil). Data were analyzed by analysis of variance and the average compared by Tukey test, with level of significance was set at (P < 0.05). For room temperature data, relative humidity, rectal temperature and for the areas of the body we used Pearson correlation (P < 0.05). For climatic factors, among the samples, room temperature and relative humidity, there was a significant difference (P < 0.05). To the skin surface temperatures of the body areas examined: vulva, pelvis, ischium, abdomen, thorax and mammary gland, among the samples, there were differences (P < 0.05) with lower temperatures of the areas in March and May samples, compared to the months of January, February and April. The average temperatures of the surfaces of the examined areas vary for the vulva between 33°C and 38°C; ischium, pelvis and abdomen between 30°C and 37°C; teats between 28°C and 37°C; Cistern of mammary quarter between 32°C and 38°C; and thorax from 31°C to 37°C. There were significant correlations between: rectal temperature x room temperature (r= 0.49; P < 0.01); Rectal temperature x relative humidity (r= -0.37; P < 0.01). To the surface temperatures of all areas of the body examined, there were significant correlations with the room temperature between (r= 0.73 and r= 0.85; P < 0.01); and between (r= - 0.57 and r= - 0.75; P < 0.05) for the relative humidity. Discussion: The animals showed no behavioral change during the thermography examination. In dairy cattle it is recommended the use of infrared thermography as a routine test to measure the temperatures of the areas of the body. Climatic factors, room temperature and relative humidity influence the rectal temperatures and the body surfaces of the cows. The areas of the body examined by infrared thermography showed different temperatures, in the same data collection, showing physiological temperature variations that assist in the clinical evaluation of each of the areas examined. The thermographic images were saved and processed easily, quickly and in a practical way, recommending the use of thermal imaging by infrared for routine as imaging test complementary to the clinical examination of the mammary gland and of the body areas in dairy cattle.